THE ADVENT OF ARTIFICIAL INTELLIGENCE IN ORAL PATHOLOGY - George-Alexandru Maftei; Maria-Alexandra Martu; Oana-Elena Ciurcanu; Alexandra Busuioc; Elena-Odette Luca; Andreea Onofrei; Ana-Maria Sciuca; Cristina Popa (Romanian Dental Association for Education, 2024)
The medical and dental fields are experiencing a significant shift in approach thanks to the integration of artificial intelligence (AI). With a vast influx of patient data, there is a pressing need for sophisticated software capable of organizing and preserving this information effectively. The emergence of AI-driven models and computer vision techniques for identifying patterns in clinical and histopathological images related to oral pathology lesions holds promise for enhancing diagnostic accuracy and prognostic predictions. While microscopic morphology remains the gold standard in diagnostic pathology, its reliance on individual pathologists introduces variability. Consequently, AI presents a potential solution for achieving consistent and more precise diagnoses. Moreover, by analyzing extensive data from the patients' medical chart the artificial neural network could provide a presumptive diagnosis and an invaluable screening tool in predicting individual risk for oral pathology based on information regarding their risk factors, systemic diseases and conditions and clinical pathological data. Within oral and maxillofacial pathology, AI stands poised to elevate diagnostic accuracy, tailor treatment, and ultimately enhance patient outcomes. Nevertheless, the integration of AI in healthcare demands meticulous attention to ethical, legal, and regulatory complexities. Moreover, given the nascent nature of AI technology, prudence is paramount when deploying it in this specialized domain.